Forschungen im Hunza-Karakorum: Vorläufiger Bericht über die wissenschaftlichen Arbeiten der Deutsch-Österreichischen Himalaya-Karakorum-Expedition 1954 - Paffen, Karlheinz; Pillewizer, Wolfgang; Schneider, Hans-Jochen (ERDKUNDE, 1956)
Between ehe areas which had been investigated by German scientific expeditions in the Pamir, Hindukusch, norch-western Himalaya and south-eastern Karakorum, there still existed a gap in the north-western Karakorum. To close this gap was the aim of the GermanAustrian Himalaya-Karakorum Expedition, 1954, which consisted of one group of seven mountaineers and another of four scientists. The first and most fundamental task was to make a map on a scale of 1 : 100,000 of an area of about 3,000 sq. Km. The very difficult task of triangulation was accomplished 1:-y K. Heckler who, while returning, met with a fatal accident in the Hunza gorge on 26 July 1954. He and W. Pillewizer together carried out the photogrammetric survey, the results of which are at present being plotted. H. ]. Schneider and K. Wienert carried out earth magnetic measurement at 132 stations in a north-south profile across the north-western Karakorum; no particular anomalies were encountered. In the north-western Karakorum which, according to its tectonic development, lies between the early consolidated Pamir and the Himalaya range which has been very active tectonically until most recent times, Schneider distinguished in a north-south sequence the following north-west-south-east striking zones: V the late paleozoicmesozoic sedimentary zone of the Tethys Karakorum; IV the axial granodiorite massif of the Karakorum main crest; III the highly metamorphic schist mantle; II the lesser metamorphic schist zone of the Hunza longitudinal valley depression; I the crystalline series of the Rakaposhi-Mashcrbrum chain. This asymmetrical structure is mainly due to two major tectonic epochs; an older prealpine, lasting until the middle carboniferous period, and the alpine, post-upper cretaceous main folding of the Karakorum system. Although no intensive study of the relief features was possible, the three authors were nevertheless able to make many geomorphological observations. For instance, the marked dependence of the relief forms on the lithological zones is remarkable, as are the absence of planation surfaces of great extent and the occurrence of several, some 1,000 m. deep, antecedent transversal and longitudinal valley sections forming part of a pre-Pleistocene valley system. Above 4,000 m. there are at some levels remains of a pre-Pleistocene relief. Very problematical is the question of the extent and age of the recent mountain uplift and valley incision which, in the longitudinal Hunza valley, probably amounts to as much as 2,000 m. On the whole, however, it must have been completed at the height of the Pleistocene period. As compared with the present day snow line at 5,000 m., the snow line during the last glaciation was about 1,000 m. lower. It was proved that, north of the main chain, where cirque glaciers prevail, this resulted in a rise of the glaciation by several 100 m., whereas south of the chain, with the prevailing avalanche fed glaciers without cirques, the rise amounted to barely 100 m. Consequently the longitudinal Hunza valley remained free of ice during the last glaciation. W. Pillewizer observed that today the contrast in the glacier types is expressed in a pronounced oscillation of the glaciers on the southern side and a balanced regime of the glaciers on the northern side. Measurements of glacier movement and ablation will provide data for calculating the amount of precipitation in the high regions. These are beyond the range of influence of thc Indian monsoon; cyclones coming from the west are the main agents responsible for precipitation during spring and summer. The study of the vegetation of the Hunza region by K. H. Paffen had the following three objectives: collection of the flora; a general view of the plant associations and their ecological conditions; and preparation of a vegetation map. In comparison with the Nanga Parbat district this region was shown to be poorer in flora by 40-45 per cent., which physiognomically showed itself in the fact that many species of trees and shrubs were absent. The vertical zoning of vegetation is asymmetrically developed on adret and ubac slopes; only on slopes with a northern or western aspect is it fully developed and shows the sequence from semi-arid desert • steppes at the valley bottom, to Artemisia and wood steppe, humid temperate coniferous forest, sub-alpine birch willow and ash scrub and cool-humid alpine zone. Corresponding with the northward increasing aridity, the altitudinal limits of the vegetation zones also increase, those of the lower zones to a greater degree than those of the higher, so that the humid arboreal zone becomes increasingly smaller and eventually disappears. On the return trip to Rawalpindi it was possible to enlarge the vegetation profile (cf. plate) across the northwestern Karakorum and Himalaya into the foreland. In this context the main Himalaya crest proved to be a climatic, vegetation and landscape boundary of the first order. On the way back W. Pillewizer carried out photogrammetric measurements on the Rakhiot glaciers to enable a comparison to be made with those of R. Finsterwalder in 1934. Besides studying problems of physical geography K. H. Pa/ Jen paid attention to the cultural landscape, which presents many problems and would really require a separate study, especially if the social structure is also to be considered. The main settlement zone, with a chain of irrigation oases, lies in the longitudinal Hunza valley between 2,000 and 2,500 m. in altitude; around 3,000 m. are dispersed settlements with arable cultivation in summer, and up to 3,800 m. many summer grazing settlements exist in the side valleys. The arable cultivation is intensive both as regards labour as well as the use of the fields themselves; two crops of bread grain are harvested annually. After the winter wheat, which prevails in lower altitudes, the catch crop is buckwheat, whereas spring barley, which dominates in the higher altitudes, is followed by millet or maize. The second source of food is the widely practised fruit cultivation in which apricots and mult berries take first place. The number of livestock fed mainly on natural pasture is considerable but as a result of the poor quality of the fodder the yield is fairly low. The highly developed rural cultural landscape stands in pronounced contrast to the primitive and unpretentious material civilisation of the Hunza popuhtion, which is highly diversified linguistically and racially as well as regards religion.